الإعجاز البلاغي في الفاصلة القرآنية(الفاصلة اللفظية والمعنوية) سورة القيامة نموذجا - Mohd Hisyam Bin Abdul Rahim
The term "Fasilah" refers to the final words in a Quranic verse. It plays an import role in preserving the perfection of the meaning and arrangement of verses. This research has three objectives which are closely related to "fasilah". The first objective is to clarify the true nature of "fasilah(s)" in the Holy Qur'an. The second objective is to reveal the beauty of "fasilah" by explaining the functions of the pronunciations and meaning. Lastly, the objective of the study is to illustrate the findings of the beauty of "fasilah" gathered through the analysis of the al-Qiyamah verse. The library research and content analysis with the practical has been compiled with practical has been compiled in this research. However, this research is different from previous ones because its attempts to analyse fasilah from its pronunciation and meaning functions. The research also analyse a specific verses in detail in the process of determining the functions. Among the findings gathered in this research are; fasilah(s) in the Holy Quran have apparently natural musical strength. The balance between rhythm and the bond of pronunciation and meaning of the fasilah signifies the beauty of 'Ikjaz Balaghi which can be found in the Holy Quran. In addition, the research conducted in the al-Qiyamah verse has revealed that fasilah in the Holy Quran invokes an intense feeling in the souls of readers through the strong bond between pronunciations and meaning also the balance of rhythm.